Ovarian Tissue Vitrification: Modalities, Challenges and Potentials - Posillico, Sarah; Kader, Amr; Falcone, Tommaso; Agarwal, Ashok (Current Women's Health Reviews, 2010)
Ovarian tissue cryopreservation is the key step towards the establishment of an ovarian tissue bank or the preservation of ovarian tissue for patients scheduled for gonadotoxic cancer therapies, aiming for fertility restoration later on. Conventional cryopreservation, or slow freezing, has been the mainstay of ovarian tissue cryopreservation. Vitrification has recently emerged as a new trend for biological specimen preservation. It has shown increasing success over slow freezing, especially with oocytes, which is mainly attributed to avoiding ice formation. Much research is underway to investigate the application of vitrification to ovarian tissue. Ovarian tissue vitrification may have specific challenges and requirements that differ from single cell or oocyte vitrification. The medical literature was searched for studies on ovarian tissue vitrification using the keywords: ovary, ovarian tissue, transplantation, vitrification, cryopreservation, and freezing. After author's agreement, relevant citations were analyzed. Thirty studies reported the ovarian tissue vitrification of 11 species, using different vitrification methods and different outcome measures. The vitrification of ovarian tissue is a promising alternative to slow freezing. However, proper ovarian tissue preparation and the specific method of vitrification are both key factors that determine the viability and functionality of preserved tissue in other applications, notably transplantation.
Keywords: autotransplantation